Prevalence of risk factors for the occurrence of strokes in the elderly - Viviane de Souza Pinho Costa; Priscila Soares Ramos Guimarães; Karen Barros Parron Fernandes; Vanessa Suziane Probst; Audrey de Souza Marquez; Dirce Shizuko Fujisawa
Introduction Stroke (CVA) is a multifactorial disease, where the combination of risk factors may be associated with and contribute to its development. Objectives The objective of this study was to evaluate the prevalence of risk factors for stroke in the physically independent elderly in the city of Londrina, Brazil. Materials and methods This study was composed of the elderly individuals participating in the EELO project (Age and Ageing Study, Londrina, State of Paraná, Brazil). In order to identify the risk factors for stroke, one used a structured questionnaire with information about socio-demographic and anthropometric data as well as lifestyle variables, such as physical inactivity and smoking, presence of comorbidities, and laboratory tests for diagnosis of diabetes and dyslipidemia. Results The study included 454 elderly with mean age of 69.7 years. There was a significant relationship between the number of risk factors and gender (p = 0.01), with higher prevalence among women. In separate analysis, the elderly between 60 and 69 years had a higher incidence of obesity (p = 0.03) and dyslipidemia (p = 0.04). Regarding gender, obesity (p = 0.01), smoking (p = 0.0001), vascular disease (p = 0.0001) and heart disease in the family (p = 0.01) higher incidence was shown in females, according toChi Square's test. Conclusions It is concluded that elderly people aged less than 70 years and older women were those with the highest number of risk factors for CVA. Therefore, it may be suggested the development of primary care programs in order to promote information on the prevention of these risk factors and thus reduce the occurrence of stroke.